68 This programe was delivered through the GSTT school of improvement (postgraduate medical education) in a london teaching hospital with a large cohort of foundation and specialist trainee doctors. The most recent national trainee survey 2018 has documented. (12th November 2018) - Rajasingam, Daghni; Cheshire, Anna; Peters, David
Abstract : This programme was delivered through the GSTT School of Improvement (Postgraduate Medical Education) in a London teaching hospital with a large cohort of foundation and specialist trainee doctors. The most recent national trainee survey 2018 has documented that significant numbers of doctors in training are burnt out and stressed by their clinical work. This impacts on the quality and safety of care provided in an already 'stressed NHS'. Resilience workshops were delivered as part of mandatory training (through a bespoke, evidence based workshop) for all foundation year doctors and the trust's junior doctor leadership group.Follow up with qualitative questionnaire occurred after the workshop. Questionnaires were used to collect quantitative and qualitative data from participants at three time points: immediately prior the workshop (baseline), immediately after the workshop (post workshop), and two months after the workshop (follow-up). Outcome measures collected included perceived stress and positive well-being scales. The participants reported high levels of stress at baseline with comparisons between baseline and 2 month follow-up questionnaires revealing improved stress levels and well-being ratings. 81% of participants felt that that topics covered were useful for their work and over three-quarters of participant said that they intended to use some of the techniques they had learnt on the workshop. 76% of those who completed a follow-up questionnaire had actually done something differently. This workshop which covered the neurobiology of resilience, the performance curve and a resilience inventory was particularly suited to addressing the needs of doctors who are familiar with the science behind evidence based interventions. This systemic approach to addressing resilience across the workforce needs to be an integrated generic component of postgraduate medical training if we are to future proof the NHS to continue delivering high quality, safe care to patients.